Targeting transcription factors for therapeutic benefit in rheumatoid arthritis - Balendran, Thivya; Lim, Keith; Hamilton, John A.; Achuthan, Adrian A. (Frontiers in Immunology, 2023)
Rheumatoid arthritis (RA) is a destructive inflammatory autoimmune disease that causes pain and disability. Many of the currently available drugs for treating RA patients are aimed at halting the progression of the disease and alleviating inflammation. Further, some of these treatment options have drawbacks, including disease recurrence and adverse effects due to long-term use. These inefficiencies have created a need for a different approach to treating RA. Recently, the focus has shifted to direct targeting of transcription factors (TFs), as they play a vital role in the pathogenesis of RA, activating key cytokines, chemokines, adhesion molecules, and enzymes. In light of this, synthetic drugs and natural compounds are being explored to target key TFs or their signaling pathways in RA. This review discusses the role of four key TFs in inflammation, namely NF-κB, STATs, AP-1 and IRFs, and their potential for being targeted to treat RA.